Feasibility Study Of Bapak Gunoto's Know Business In Lebong District - Redi, Redi; Irwanto , Tito; Abi , Yudi Irawan (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the feasibility study of Mr. Gunoto's Tofu Business in Lebong Regency. The analytical method used is a feasibility study analysis from the financial aspect which includes Net Present Value (NPV), Internal Rate of Return (IRR), and Gross Benefit Cost Ratio (Gross B/C).The results of the Net Present Value (NPV) research show a positive number of Rp. 339,819,380,-, meaning that the expansion of Mr. Gunoto's Tofu Business in Lebong Regency can be said to be feasible for development. IRR (Internal Rate of Return) is known to be 30% greater than the percentage cost of capital (loan interest), namely 12% or 16%, meaning that business expansion is feasible for development. This shows that if funds for investment are saved or deposited in a bank with an interest rate of 12% and an interest rate of 16%, then the capital will grow faster if it is made into tofu business capital because it will grow at an interest rate equivalent to 30. Gross B/C greater than 1 (1.69 > 1) means that the development of Mr. Gunoto's tofu business in Lebong Regency is feasible for development.